A Pharmacy-Only Refill Program at a Large HIV Clinic in Uganda: Experience and Satisfaction of Patients. (May 2014) - Nakiwogga-Muwanga, Alice; Katabira, Elly; Sempa, Joseph; Kambugu, Andrew; Nakibuuka-Lubwama, Esther; Lamorde, Mohammed; Mawejje, Joseph; Colebunders, Robert
Background: The purpose of this study was to assess patients' experience and satisfaction with pharmacy-only refill program (PRP) and to compare those who were removed from the PRP with those still in the program. Methods: A sample of 446 patients was selected from 1503 patients on antiretroviral therapy that had been enrolled in the PRP for at least 24 months. The study used interviewer-administered questionnaires to assess patients' experience and satisfaction with PRP. Results: Of the 446 patients, 133 (29.8%) were removed from the PRP. By multivariate analysis, it was found that wanting to see a clinician before their scheduled clinic visit, Christian religion, and not understanding why they were enrolled in PRP were associated with having been removed from the PRP. Patients felt that the greatest benefit from the program was the time that they saved to do other activities. Patients preferred to collect their medication every 3 months instead of every month. Conclusion: All patients interviewed scored the program high, and all recommended that the PRP should continue. Stable patients prefer to see clinicians less frequently and visit clinic less often.